2018
DOI: 10.1097/anc.0000000000000484
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Underrunning Water Bathing and Immersion Tub Bathing on Vital Signs of Newborn Infants

Abstract: Background: Newborn infants are susceptible to hypothermia during bathing due to environmental conditions. Purpose: This study examined the effects of 2 common newborn bathing methods used in Turkey, underrunning water bathing (URWB) and immersion tub bathing (ITB), on infant heart rate (HR), oxygen saturation, and body temperature. Methods: In this randomized controlled study, 44 newborns were allocated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 20 publications
1
15
1
6
Order By: Relevance
“…In our study, it was found that the body temperature of the SB group decreased less compared to the TB group in the post‐bath period compared to pre‐bath period; however, the difference between them was not statistically significant. In the study by Ar and Gözen (2018) on the effects of running water bathing and SB on vital signs of term newborns in the intensive care unit, it was reported that although the difference was not significant, the body temperature of the newborns in the SB group increased at the 20th minute and they got out of cold stress earlier compared with the other group. In the study by Edraki et al (2014) to compare the running water bathing and the SB methods in preterm newborns, it was reported that there was no significant difference between the post‐bath and pre‐bath body temperatures of the newborns in the SB group while a significant difference was observed between the post‐bath and pre‐bath body temperatures of the newborns in the running water bathing group.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In our study, it was found that the body temperature of the SB group decreased less compared to the TB group in the post‐bath period compared to pre‐bath period; however, the difference between them was not statistically significant. In the study by Ar and Gözen (2018) on the effects of running water bathing and SB on vital signs of term newborns in the intensive care unit, it was reported that although the difference was not significant, the body temperature of the newborns in the SB group increased at the 20th minute and they got out of cold stress earlier compared with the other group. In the study by Edraki et al (2014) to compare the running water bathing and the SB methods in preterm newborns, it was reported that there was no significant difference between the post‐bath and pre‐bath body temperatures of the newborns in the SB group while a significant difference was observed between the post‐bath and pre‐bath body temperatures of the newborns in the running water bathing group.…”
Section: Discussionmentioning
confidence: 95%
“…These results suggested that SB was effective in the retaining of HR within the desired range with the further soothing of the newborn and accordingly on the increase in SpO2. When the literature was reviewed, it was observed that TB method performed by the nurses with term and preterm babies in the hospital environment was generally more effective in soothing the newborn compared to other bathing methods (Ar & Gözen, 2018; Bryanton et al, 2004; So et al, 2014). Furthermore, swaddling helped newborns to be more comfortable and stress‐free.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature has investigated the effects of bathing type on body temperature (Anderson et al., 1995; Ar & Gözen, 2018; Loring et al., 2012; Penny‐MacGillivray, 1996; Tapia‐Rombo et al., 2003, 2012), crying time (Erdaki et al., 2014), stress or comfort (Bryanton et al., 2004; Taşdemir & Efe, 2019), and umbilical cord health (Ayyildiz et al., 2015). There are also studies on the effects of baby bathing products on infants (Cole & Brissette, 1999; Liaw et al., 2006; Lund et al., 2020).…”
Section: Introductionmentioning
confidence: 99%